INNOVATION POTENTIAL OF SMALL INDUSTRIES IN THE PARADIGM OF INCLUSIVE DEVELOPMENT IN INDONESIA - Asmara, Indri Juwita; Berliana, Nani Grace; Ariana, Lutfah; Rahmaida, Rizka (Pusat Penelitian Perkembangan Iptek, LIPI, 2013)
Inclusive development is a development prioritized to alleviate poverty and to encourage all community groups to contribute in creating opportunities, benefits, and participation in decision-making. Small industry is one of the target groups prioritized in inclusive development, especially in the creation of innovation. This paper aims to map the innovation potential of smallindustry in Indonesia. Potential innovations are represented by several indicators, namely: industrial resources obtained, innovation activities and industrial cooperation with the provider of science and technology. Innovation potential of small industry in Indonesia is still not statistically well identified. Therefore, this paper seeks to provide a preliminary description of the innovation activities in small industry. The data used as the basis of the analysis is synthesized from the innovation survey ofmanufacturing industry in Indonesia conducted in 2011. Total of 1.375 respondents, 556 respondents are identified as small industry. Out of the total, 350 small industry declares innovation activities both technological innovation and nontechnological innovation. Using descriptive analysis, it is known that small industry innovation activities are quite diverse ranging from: the acquisition of knowledge, human resource training, and intramural R & D activities. This indicates that the industry has potential for inclusive development.